Potential Cost-Savings From the Use of the Biosimilars in Slovakia - Tesar, Tomas; Golias, Peter; Kobliskova, Zuzana; Wawruch, Martin; Kawalec, Paweł; Inotai, András (Frontiers in Public Health, 2020)
Objectives: To analyse the market shares of biosimilars in Slovakia and to calculate the potential cost-savings from the use of biosimilars in Slovakia based on two different data sources. Methods: National reimbursement lists from the Czech Republic, Hungary, Poland and Slovakia were used for analysing the availability of biosimilars with public funding. In addition, the reimbursement dossiers of biosimilars, the justifications of reimbursement decisions by the Slovak Ministry of Health, and final reimbursement decrees, which are published on the webpage of the Slovak Ministry of Health, were utilized for this study. Reimbursement decisions regarding biosimilars by the Slovak Ministry of Health from 2006 to August 2019 were considered and the detailed utilisation of biosimilars in 2018 was analysed based on data from the State Institute for Drug Control. The study was validated based on data from the Slovak National Health Information Centre. Results: 54 biosimilars were approved by the European Medicines Agency (EMA) in August 2019. Of the total group of licensed biosimilars on the market, 29 biosimilars (54%) were available in the Czech Republic, 28 biosimilars (52%) were available in Poland, and 27 biosimilars (50%) were available in Hungary and 24 biosimilars (44%) were available in Slovakia. Our analysis, based on the data provided by distributors of medicinal products to the State Institute for Drug Control, revealed that the health fund in Slovakia could have saved 35 to 50 million euros per year if biosimilars with marketing authorisations had been available on the Slovak market. The calculations assumed a 25 to 35% price decrease against the original biological medical products, and that there would be no increase in the utilisation of biosimilars in Slovakia. Conclusions: To achieve significant improvement in patient access to biosimilars in Slovakia, a top-down approach establishing targets and quotas for the procurement of biosimilars should be applied.